2023
DOI: 10.2340/actadv.v103.9604
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the rs1800440 Polymorphism in CYP1B1 Gene and the rs9258883 Polymorphism in HLA-B Gene in a Spanish Cohort of 223 Patients with Frontal Fibrosing Alopecia

David Saceda-Corralo,
Daniel Ortega-Quijano,
Gloria Muñoz-Martín
et al.

Abstract: The pathogenesis of frontal fibrosing alopecia has been linked to specific genetic variants. CYP1B1 codes for a component of the cytochrome p450 machinery that is involved in the metabolism of xenobiotic oestrogens. The study of the prevalence of polymorphisms in this gene may help to understand their role in the development of frontal fibrosing alopecia. The aim of this study is to describe the frequency of genetic variations in the alleles HLA-B*07:02 and CYP1B1 in patients with frontal fibrosing alopecia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A study conducted on 233 FFA patients upheld this by identifying that the vast majority of FFA patients (75.2%) did not have the protective rs1800440 polymorphism in CYP1B1. Furthermore, it also reported that 83.8% of the subjects carried the rs9258883 polymorphism in HLA-B*07:02, which is involved in a deviant immune response, thus the genetic component is further demonstrated [97]. CYP1B1 selectively catalyzes the 4-hydroxylation of estradiol and is highly expressed in estrogen target tissues, such as the ovary, uterus, and mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on 233 FFA patients upheld this by identifying that the vast majority of FFA patients (75.2%) did not have the protective rs1800440 polymorphism in CYP1B1. Furthermore, it also reported that 83.8% of the subjects carried the rs9258883 polymorphism in HLA-B*07:02, which is involved in a deviant immune response, thus the genetic component is further demonstrated [97]. CYP1B1 selectively catalyzes the 4-hydroxylation of estradiol and is highly expressed in estrogen target tissues, such as the ovary, uterus, and mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…FFA has been the subject of genetic scrutiny for approximately a decade, initially explored through brief publications and case reports [ 23 ]. Familial patterns and cases in monozygotic twins have been reported, suggesting a genetic component [ 10 , 24 , 25 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Saceda-Corralo et al conducted a cross-sectional study with 223 patients affected by FFA and determined that a total of 83.8% of patients with FFA carried the rs9258883 polymorphism in HLA- B*07:02, and the majority of them lacked the protective rs1800440 polymorphism in CYP1B1 (75.2%) [ 23 ]. Indeed, it seems that some patients possess protective alleles associated with the CYP1B1 gene (e.g., p.Asn453Ser), which could influence FFA risk [ 27 ].…”
Section: Etiopathogenesismentioning
confidence: 99%